Assessing the sensitivity of riparian algarrobo dulce (Prosopis flexuosa DC) radial growth to hydrological changes - Piraino, Sergio (2016)
Ecotones, as for example riparian zones, have long interested ecologists, due to their potential role in generating species biodiversity and evolutionary novelty, as well as their sensitivity to environmental changes. Along riparian areas, vegetation is recognized for its ecological importance in several ecosystemic processes. In the Central Monte Desert (central-west Argentina), Prosopis flexuosa grows in territories characterized by a permanent access to water reservoirs, e.g. along riverbanks, where the species forms the classic gallery forests. Despite the ecosystemic role of the different Prosopis species distributed in arid lands, thus far no analysis has been conducted regarding the relation between their radial growth and hydrological changes, namely streamflow variability, in riparian settings. To fill this gap of knowledge, we performed a dendrochronological analysis considering several riparian P. flexuosa trees differing in their spatial position in relation to the riverbank. Pointer years, correlation function, and regression analyses show differences in the dendrohydrological signal of the studied species, probably function of tree distance from the river. In this sense, radial growth of trees distributed near the riverbank is tightly coupled to spring-summer (September to March) stream-flow variability, whereas for farthest trees the ring development is driven by a combination of winter and spring river discharge and late-summer precipitation amount. The presented results demonstrate the potentiality of P. flexuosa, and in a broader sense of the Prosopis genus, in dendrohydrological studies.